Des expérimentations légitimées par le traumatisme : Paul Léon à Saint-Remi de Reims - Camille Bidaud (In Situ)
This article is a study of the architectural services at the French Sous-Secrétariat des Beaux-Arts, headed by Paul Léon, who has considerable importance in the protection and reconstruction of historic monuments in territories close to the front during the First World War. The article concentrates in particular on the city of Rheims. The official doctrine of the Historic Monuments administration, hitherto entirely devote to conservation, was forced to evolve on account of the numerous restorations immediately after the war, as we shall see with the case of Saint-Remi of Rheims. During the war and after it, Paul Léon used his studies and restoration work as propaganda tools.